HISTORY OF KHORAZM GLASSWORK (E Conference Zone, 2024)
This article analyzes the period of Khorezm glassmaking from ancient times to the beginning of the 13th century AD. In the territory of ancient Khorezm, various objects were made of glass starting from the Bronze Age. Initially, beads, rings, amulets, medallions, plates for fastening on window sills, glass vessels in the form of amphoras were found. Workshops, artifacts and slag related to the craft of glassmaking were studied. It is shown that glass production was started by craftsmen in the Khorezm territory.